Pemaknaan Proses Menuju Opini WTP - Teri Teri; Wawan Darmawan (Journal of Applied Accounting and Taxation, 2017)
Government South Sulawesi Province has obtained WTP opinion for the four consequentive years. This research aimed to interpret the meaning of the auditor’s proper without-exception (WTP) opinion from the point of view of the understanding of the writer of the financial statements (BPKD) and the Inspectorate of the Government of South Sulawesi Province. The research samples (informants) were the staff members and achelon officials in the Government of South Sulawesi Province, the echelon officials in the inspectorates of South Sulawesi Province. The research type was qualitative, and the researcher tried to dig the meaning of the WTP opinion which was achieved Maynard’s thought, in which Maynard analyzed the conversation. The qualitative data were analyzed in the three steps, namely (1) the data reduction, (2) the data display, and (3) the conclusion drawing/verification. The research result revealed that the WTP opinion achieved by the Government of South Sulawesi was started from the leader’s ambision to achieve the WTP opinion while he was in his position. Socially, all the civil achieve the WTP opinion. Psychologically, such a situation had made some of the staff members had showed different behaviors: some as well as the echelon did the work voluntary, but some did it because of the pressure of their superior.